Caracterización y evaluación de la sustentabilidad del sistema de producción de leche, de treinta familias del barrio La Libertad de la parroquia, José Guango Bajo, cantón Latacunga, 2020- 2021. - Proaño Coba, Carla Vanessa (2023)
This project was carried out in the neighborhood of La Libertad, parish of José Guango, with the aim of characterizing and evaluating the sustainability of the milk production system for 30 producer families. In the characterization it was determined that the UPA's are mainly dedicated to livestock activity as the main source of economic income where 86.67% of the families are dedicated to the production of milk which produce 15 to 30 liters of milk daily whose cost vary from 0.35 to 0.40. On the other hand, in agricultural activity, its predominant crops are pastures as the main source of food for livestock. In the social aspect, it was determined that the production units are managed by 80% for women, there is also a low schooling rate with a value of 76.67%, which have primary education, generating a low rate of schooling, another determining factor is that most producers do not have large areas of land and have extensions of less than one hectare making it difficult for them to generate greater pasture production and therefore the increase of the cattle herd.